USING PODCAST WITH DICTOGLOSS PROCEDURES TO IMPROVE LISTENING COMPREHENSION AND WRITING ACHIEVEMENTS OF TENTH GRADERS - Haritsah Sani; Rita Inderawati; Machdalena Vianty (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2016)
Abstract: The aim of this experimental study was to investigate whether or not there was a significant improvement in students’ listening comprehension and writing achievements after being taught by using podcast with dictogloss procedure and a significant difference in listening comprehension and writing achievements of the students who got the treatment and those who did not. This study also investigated which aspects of listening comprehension and writing that had contribution towards the students’ achievements. The population of this study was all of the tenth graders of SMA Negeri 22 Palembang in academic year 2015-2016. Forty students with similar listening proficiency level were selected as the sample by using purposive sampling method. They were divided equally into experimental and control groups. Pretest and posttest were given to both groups, but only the experimental group was taught by using podcast with dictogloss procedure as the treatment. The data were obtained from listening comprehension and writing pretests and posttests in both groups and were analyzed by using both paired and independent sample t-test, and linear regression. The results showed that there were a significant improvement in listening and writing achievements in the experimental group. However, there were a significant different in listening (mean difference=11.050, p=0.006) and writing (mean difference=27.850, p=0.000) achievements between both groups. In addition, all of aspects of listening and writing gave a significant contribution to the students’ achievements after getting the treatment. Keywords: listening comprehension, writing, podcast, dictogloss procedure